2020
DOI: 10.7189/jogh.10.010403
|View full text |Cite
|
Sign up to set email alerts
|

Using Google Trends to assess the impact of global public health days on online health information seeking behaviour in Central and South America

Abstract: Background Public health awareness can help prevent illness and result in earlier intervention when it does occur. For this reason, health promotion and disease awareness campaigns have great potential to alleviate the global burden of disease. Global Public Health Days (GPHD) are frequently implemented with this intent, but research evaluating their effectiveness, especially in the developing world setting, is scant. Objectives We aimed to evaluate the impact of four GPHDs (World Cancer Day, World Diabetes Da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 37 publications
2
49
0
1
Order By: Relevance
“…Nuti et al have previously found that a large multitude of papers lack the information needed to make them fully reproducible ( Nuti et al, 2014 ). Nevertheless, Google Trends has served and still serves as an excellent tool for infoveillance and infodemiology: in fact, even admitting that newspapers and newscasts can influence web queries, it provides a way to quantify the web interest in a specific topic more efficiently than any other methods historically used (e.g., population surveys) ( Amber et al, 2016 ; Dreher et al, 2018 ; Mohamad and Kok, 2019 ; Havelka et al, 2020 ). Moreover, it can be used as a complement to a traditional analysis ( Schootman et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nuti et al have previously found that a large multitude of papers lack the information needed to make them fully reproducible ( Nuti et al, 2014 ). Nevertheless, Google Trends has served and still serves as an excellent tool for infoveillance and infodemiology: in fact, even admitting that newspapers and newscasts can influence web queries, it provides a way to quantify the web interest in a specific topic more efficiently than any other methods historically used (e.g., population surveys) ( Amber et al, 2016 ; Dreher et al, 2018 ; Mohamad and Kok, 2019 ; Havelka et al, 2020 ). Moreover, it can be used as a complement to a traditional analysis ( Schootman et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…The independent variable was the Day ID, where the 29th of the 36 days represented the GPHD and the dependent variable was set to be the RSV value. The model assumed that the errors have a constant variance, and the number of joinpoints was set for a minimum of zero and a maximum of three [ 15 ]. The minimum number of observations from a joinpoint to either end of data was set to two and the minimum number of observations between joinpoints was also set to two.…”
Section: Methodsmentioning
confidence: 99%
“…No logarithmic transformation was applied to the data. For countries without trends, an average RSV value was calculated across the time period of 36 days [ 15 ]. One-way analysis of variance (ANOVA) was used to assess any significant differences in the mean of RSV values between the selected countries for each GPHD.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…in fact, even admitting that newspapers and newscasts can influence the trends of web queries, it provides a way to quantify the web interest in a specific topic more efficiently than any other methods historically used (e.g. population surveys) [21][22][23][24]. Moreover, it can be used as a complement to a traditional analysis [25].…”
Section: Italian Cities' Web Interest During Period 1 and Periodmentioning
confidence: 99%